Formulation and Evaluation of Polymeric Ornidazole Floating Microspheres: A Comprehensive Approach - Waghmode, Raghwendra; Hingmire, Rushikesh; Yeligar, Veerendra; Barde, Sandeep (Indian Journal of Pharmaceutical Education and Research, 2026)
Aim/Background: Ornidazole is primarily used to treat peptic ulcer. Ornidazole laden floating microspheres were developed to boost bioavailability of the therapeutic moiety and its appropriate therapeutic performance. Materials and Methods: Solvent evaporation approach was utilised to fabricate the gastroretentive floating microspheres using different polymers such as HPMC K100M, Eudragit RS100 and ethyl cellulose. It was also brought to light that the formulation of the ornidazole microspheres delayed therapeutic release for 12 hr. Prepared formulation characterised for SEM, micromeritic characteristics, in vitro release experiments, short-term stability studies, (%) yield, drug content, drug entrapment efficiency, drug loading. All characteristics showed promising results at wrap of the study. Results: Investigations revealed that, formulations containing Eudragit RS100 showed superior floating microspheres and drug release characteristics. The optimised formulation F3 show 83.45±0.47% entrapment efficiency, 170.3 μm particle size, and 94.58% cumulative percent drug release. Results were confirmed experimentally. Conclusion: The study concluded that the developed floating microspheres for ornidazole exhibited enhanced cumulative drug release, ultimately enhancing bioavailability.
Keywords: Particulate Drug Delivery; Floating microspheres; Synthetic polymers; Solvent; Evaporation method